(untitled) (Móin-Móin Magazine - Studies in the Art of Puppetry, 2024)
This article seeks to reveal the procedures for popularizing the Lambe-lambe Theater in Amazonas based on the Extension Project, running since 2021, firstly in a telepresence format and, from 2023, in person. It reports on the first steps of language in Amazonas, relating study, research and practice with artists, students, teachers and curious people, in order to highlight the importance of university extensions as a space for dialogue with the community and the promotion of knowledge.